Sexual health outcomes after penile reconstruction in the exstrophy–epispadias complex. Issue 6 (December 2022) - Harris, Thomas G.W.; Khandge, Preeya; Wu, Wayland J.; Leto Barone, Angelo A.; Manyevitch, Roni; Sholklapper, Tamir; Bivalacqua, Trinity J.; Burnett, Arthur L.; Redett, Richard J.; Gearhart, John P.
Summary: Introduction: The penis in exstrophy–epispadias complex (EEC) males is diminutive and patients are often dissatisfied with appearance and length. Due to an increased risk of psychosexual dysfunction, patients desire penile reconstruction. Surgical options include penile lengthening with a full thickness skin graft (SG) or tissue expansion (TE) used for cutaneous coverage or neophalloplasty using a radial forearm free flap or pedicled antero-lateral thigh flap. Objective: The aim of this study was to assess sexual health outcomes before and after SG or TE assisted lengthening and neophalloplasty. Study design: Patients aged 18 years or older, who underwent penile reconstruction were identified using an institutionally approved database of EEC patients. Patient perception of penile appearance, sexual function, their frequency of sexual intercourse and overall satisfaction with reconstruction were assessed using a survey consisting of validated and non-validated questions. Results: Eighty-three patients underwent penile reconstruction, 57 met the inclusion criteria and 28 responded to the survey (49.1%). Fourteen were reconstructed using a SG, 6 with TE and 8 underwent neophalloplasty. Median time from reconstruction to survey completion was 4.4 years (range 1.2–13.2) Four patients had a diagnosis of epispadias, 1 cloacal exstrophy, 23 classic bladder exstrophy (CBE). Before reconstruction patients were dissatisfied with their penile appearance with a median penile perception score of 4.5 compared to 7.5 after surgery (p = 0.0034, Fig. 1 ). Twenty-three patients were dissatisfied with penile length, with 18 reporting an improvement following reconstruction (p = 0.0002). There was no correlation in time after reconstruction with PPS or satisfaction with penile length (p = 0.86 and p = 0.55, respectively). Overall, the median Sexual Health Inventory for Men (SHIM) score was 19, with no difference between the surgical groups (p = 0.33). Nine patients engaged in sexual intercourse before reconstruction which increased to 17 afterwards. Conclusion: All three surgical methods improved patient perception of penile appearance and length. Patients who previously never engaged in intercourse were able to and those who had were doing so more frequently, of which a greater proportion were in a relationship. The results are encouraging though must be interpreted with caution due to the small number of responders and possible risk of bias. These findings provide vital information for future patients and routine psychological assessment will help manage patient expectations to improve satisfaction.